2014
DOI: 10.1080/09243046.2013.877778
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term exposure to high temperature atmosphere on weight change and damage progress in carbon fiber-reinforced polycyanate ester composites

Abstract: Composites degradation in thermo-oxidative environment was investigated by measuring weight change and characterized using quantitative methods. Isothermal aging experiment was conducted on carbon fiber/polycyanate (T700SC/FSD-M-08178) unidirectional, angle-ply and quasi-isotropic (QI) laminate at 180°C in air up to 1500 h. Two empirically based weight change models were used to predict weight change of unidirectional, angle-ply, and QI laminates. Microscopic observation was also conducted on exposed surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Meanwhile, bismaleimide (BMI) resin matrix composites are currently used as structural materials for both military and commercial aircraft, due to their high specific mechanical strength and stiffness under high service temperature [8,9]. This is especially the case of the future supersonic transport aircraft, which is expected to have a service life of around 80,000 h for a supersonic flight, with a maximum skin temperature of 180 °C [10,11]. At high temperatures (approaching the glass transition temperature ( T g ) of the matrix), PMCs are susceptible to oxidative degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, bismaleimide (BMI) resin matrix composites are currently used as structural materials for both military and commercial aircraft, due to their high specific mechanical strength and stiffness under high service temperature [8,9]. This is especially the case of the future supersonic transport aircraft, which is expected to have a service life of around 80,000 h for a supersonic flight, with a maximum skin temperature of 180 °C [10,11]. At high temperatures (approaching the glass transition temperature ( T g ) of the matrix), PMCs are susceptible to oxidative degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The above researches on the TOA of CF-reinforced BMI composites indicated that the specimens would show delamination damage, whether it suffered bending stress or impact stress in the aged state. This was because of mismatch of thermal expansion coefficients of fiber and resin [18], as well as the resin shrinkage [19], causing fiber/matrix interface debonding during the TOA process [12,18]. The layers in the laminated PMCs are connected only by resin, so once the adhesive force between fiber bundles and resin seriously decreases after TOA, the delamination damage easily occurs with the external load.…”
Section: Introductionmentioning
confidence: 99%
“…As the aging time increases, many cracks are generated at the fiber–matrix interface and oxygen may enter the interior of the material through these cracks, 31 thereby increasing the contact area with the resin and increasing the rate of thermal–oxidative aging. 32…”
Section: Resultsmentioning
confidence: 99%